Collaboration in Virtual Learning Environments: a proposal to contribute to the teaching and learning process in Biology (Research, Society and Development, 2021)
The challenges of the teaching and learning process in Biological Sciences have increased together with the emergence of New Methodologies for teaching. The study in Biology shows the need to develop proposals that seek a greater integration between student and teacher in order to streamline the construction of knowledge in Biology. The objective of this work is to analyze how the mechanisms of collaboration occur in the construction of knowledge in Biology in a virtual environment, among Biological Sciences' students from UEMG - Carangola Unit. With the use of methods addressed in usual methodologies of qualitative research, two questions were used problems in students of the Biological Sciences course at the University of the State of Minas Gerais (UEMG) Carangola. Data collection was facilitated by the creation of virtual rooms on the Moodle platform, from the interactions between the students, files were prepared using the NVIVO program, which allowed the development of codes and categories that provided the discussions of the work. The data show that, encouraged by our proposal, the students developed collaborative schemes, in a spontaneous way, which allowed the conclusion of the proposal. It is clear in our proposal that the challenge of seeking new propositions for the process of knowledge construction in Biology brings significant advantages for the students and allowed the teacher a greater integration with the content taught in the classroom. We believe that the proposal contributed significantly to the students' apprehension of the contents in Biology.